Application of SIDIRA Technology at the Library and Archives Service of Sidoarjo Regency: Penerapan Teknologi SIDIRA di Dinas Perpustakaan dan Kearsipan Kabupaten Sidoarjo - Syahputri, Fitriani Firman; Agustina, Isna Fitria (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study was to describe and analyze SIDIRA Technological Innovations at the Library and Readiness Service of Sidoarjo Regency. This study uses descriptive qualitative methods. The data obtained through observation, documentation, and interviews with the Head of Service Processing and Preservation of Library Materials, SIDIRA service officers and SIDIRA users. Data analysis techniques in this study are data collection, data reduction, data presentation and drawing conclusions. The results showed that SIDIRA's technological innovation in the Library and Archives Service of Kab. Sidoarjo the facilities and infrastructure used are adequate and provide many conveniences, especially for the user community. And the problem is that sometimes the SIDIRA application server down or error occurs, then the SIDIRA application must use an online network to borrow and return books, it must have a stable connection. And lastly, books in the SIDIRA application cannot be downloaded, only read on the spot.